Implementation of the competency-based curriculum by teachers of History in selected Secondary Schools in Lusaka district, Zambia (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The study investigated teachers of History’s implementation of the competency-based teaching approaches in the teaching and learning of History in Lusaka district, Zambia. A mixed-methods approach particularly the explanatory sequential design was used in this study. The study focused on schools in Lusaka from the ten zones. The total sample size of this study was 99. A total of 80 teachers participated in this study and 10 of them were interviewed. The participants were randomly and purposively selected. A questionnaire was used to gather information from the teachers. Interview guides were also used to collect data from one Chief Curriculum Specialist, one Subject Curriculum Specialist, 2 Standard Officers, 5 Head-Teachers, 10 Heads of Sections and 20 Teachers. Classroom lesson observations and document analysis were also done. Quantitative data was analysed using the statistical package for social sciences (SPSS) and qualitative data was analysed thematically. The findings of the study revealed that 67% of the teachers of History did not understand the concept of the competencybased curriculum or outcome-based curriculum. It was also revealed that teachers of History were not using the competency-based or outcomesbased approaches to a large extent in the teaching and learning of History in the selected secondary schools because they did not have the knowledge and skills of the competency-based approaches. Thus, it was recommended that the Ministry of General Education (MoGE) should strengthen the in-service training and continuous professional development meetings in schools and zones for the competency-based curriculum to be successfully understood and implemented effectively in schools.
Keywords: Competency-Based Curriculum; Teaching; Learning; History and Competences